Biogenic Control of Manganese Doping in Zinc Sulfide Nanomaterial Using Shewanella oneidensis MR-1 - Chellamuthu, Prithiviraj; Naughton, Kyle; Pirbadian, Sahand; Silva, Kalinga Pavan T.; Chavez, Marko S.; El-Naggar, Mohamed Y.; Boedicker, James (Frontiers in Microbiology, 2019)
Bacteria naturally alter the redox state of many compounds and perform atom-by-atom nanomaterial synthesis to create many inorganic materials. Recent advancements in synthetic biology have spurred interest in using biological systems to manufacture nanomaterials, implementing biological strategies to specify the nanomaterial characteristics such as size, shape, and optical properties. Here we combine the natural synthetic capabilities of microbes with engineered genetic control circuits towards biogenically synthesized semiconductor nanomaterials. Using an engineered strain of Shewanella oneindensis with inducible expression of the cytochrome complex MtrCAB, we control the reduction of manganese (IV) oxide. Cytochrome expression levels were regulated using an inducer molecule, which enabled precise modulation of dopant incorporation into manganese doped zinc sulfide nanoparticles (Mn:ZnS). Thereby, a synthetic gene circuit controlled the optical properties of biogenic quantum dots. These biogenically assembled nanomaterials have similar physical and optoelectronic properties to chemically synthesized particles. Our results demonstrate the promise of implementing synthetic gene circuits for tunable control of nanomaterials made by biological systems.